COMPARATIVE ANALYSIS OF LOAN TO DEPOSIT RATIO AND DEBT TO EQUITY RATIO AT PT. INDONESIAN PEOPLE'S BANK, TBK AND PT. STATE BANK OF INDONESIA, TBK - Yuniar, Fika Ari; Munandar, Aris; Alwi, Alwi (Universitas Riau Kepulauan, 2024)
The stability of banking institutions is very much needed in an economy. This stability is not only seen from the amount of money in circulation, but also seen from the number of banks that exist as financial management tools. For this reason, banking institutions must be able to stabilize their banking financial performance. The purpose of this research is to determine the difference between Loan To Deposit Ratio and Debt To Equity Ratio at PT. Bank Rakyat Indonesia, Tbk and PT. Bank Negara Indonesia, Tbk. The research instrument used is a list of indicator tables for the Loan To Deposit Ratio variable which contains data on total credit and third party funds, as well as the Debt To Equity Ratio variable indicator which contains data on total debt and total equity. The population used in this research is the balance sheet report of PT. Bank Rakyat Indonesia, Tbk since being listed on the IDX from 2003 to 2022, namely for 19 years and PT. Bank Negara Indonesia, Tbk from 1996 to 2022, namely for 26 years. The sample in this research is the balance sheet report of PT. Bank Rakyat Indonesia, Tbk and PT. Bank Negara Indonesia, Tbk for 10 years, namely from 2013 to 2022. The sampling technique used in this research is purposive sampling technique. Research data was collected by means of documentation and literature study and then analyzed using an independent sample t test. The research results show that there are differences in the Loan To Deposit Ratio at PT. Bank Rakyat Indonesia, Tbk and PT. Bank Negara Indonesia, Tbk.